Aisyiyah Organizational Communication in Realizing the True Islamic Society - Adhianty Nurjanah; Dyah Mutiarin; Gatot Supangkat; Muhammad Iqbal (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
Aisyiyah is a Muhammadiyah women’s organization and has a mission to fight for a true Islamic society. This study aims to determine how organizational communication is carried out by the Aisyiyah Ngampilan Branch Manager (PCA) to create a true Islamic society in Ngampilan Village, Yogyakarta. The method used in this study is the mix-method to measure the effectiveness of organizational communication carried out. The results of the quantitative data test with Standard Deviation 1.96 show that downward communication is 2.213, up is 2.321, horizontal is 2.7801, and interline is 2.8011, which has a positive and significant effect on Organizational Communication in realizing true Muslims. PCA Ngampilan realizes true Islam through various social, educational, and religious activities, Business Charities, giving compensation. In addition, PCA Ngampilan prioritizes the persuasive communication of Hablumminannas, which prioritizes good relations and helping others, so that the Aisyiyah Organization is more readily accepted in the community.